Measurement of SARS-CoV-2 in air and on surfaces in Scottish hospitals. (March 2023) - Loh, M.M.; Yaxley, N.; Moore, G.; Holmes, D.; Todd, S.; Smith, A.; Macdonald, E.; Semple, S.; Cherrie, M.; Patel, M.; Hamill, R.; Leckie, A.; et al.
Summary: Background: There are still uncertainties in our knowledge of the amount of SARS-CoV-2 virus present in the environment – where it can be found, and potential exposure determinants – limiting our ability to effectively model and compare interventions for risk management. Aim: This study measured SARS-CoV-2 in three hospitals in Scotland on surfaces and in air, alongside ventilation and patient care activities. Methods: Air sampling at 200 L/min for 20 min and surface sampling were performed in two wards designated to treat COVID-19-positive patients and two non-COVID-19 wards across three hospitals in November and December 2020. Findings: Detectable samples of SARS-CoV-2 were found in COVID-19 treatment wards but not in non-COVID-19 wards. Most samples were below assay detection limits, but maximum concentrations reached 1.7×10 3 genomic copies/m 3 in air and 1.9×10 4 copies per surface swab (3.2×10 2 copies/cm 2 for surface loading). The estimated geometric mean air concentration (geometric standard deviation) across all hospitals was 0.41 (71) genomic copies/m 3 and the corresponding values for surface contamination were 2.9 (29) copies/swab. SARS-CoV-2 RNA was found in non-patient areas (patient/visitor waiting rooms and personal protective equipment changing areas) associated with COVID-19 treatment wards. Conclusion: Non-patient areas of the hospital may pose risks for infection transmission and further attention should be paid to these areas. Standardization of sampling methods will improve understanding of levels of environmental contamination. The pandemic has demonstrated a need to review and act upon the challenges of older hospital buildings meeting current ventilation guidance.